Perpektif Pemerintah Provinsi Papua Pada Penerimaan Pemekaran Daerah Otonomi Baru Di Provinsi Papua - Tabuni, Nes; Waworundeng, Welly; Sampe, Stefanus (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the perspective of the Papua provincial government on the acceptance of the new autonomous region in Papua province. The research was conducted from March to April 2023 in Papua Province as the parent province among the three new autonomous regions. The data analysis technique used in this study is an interactive qualitative technique. The results of the research are that other regional governments also consider that the expansion of the New Autonomous Region (PDOB) in the provinces of Papua and West Papua is indeed a necessity and can be assessed as the impact of Papua's mismanagement so far. The policy of the central government must side with the regional government in Papua, but this is not democratic and does not understand the history and character of the indigenous Papuans, so that the state's goals can be fulfilled in carrying out the Expansion of the New Autonomous Region (PDOB) in Papua with political strategies that are dominated by the government with an action that can realize the ability to carry out development and welfare for the people of Papua and in general for the Indonesian state.